Arterial distensibility as a possible compensatory mechanism in chronic aortic regurgitation - Kopel,Liliane (2001)
OBJECTIVE: To evaluate elastic properties of conduit arteries in asymptomatic patients who have severe chronic aortic regurgitation. METHODS: Twelve healthy volunteers aged 30±1 years (control group) and 14 asymptomatic patients with severe aortic regurgitation aged 29±2 years and left ventricular ejection fraction of 0.61±0.02 (radioisotope ventriculography) were studied. High-resolution ultrasonography was performed to measure the systolic and diastolic diameters of the common carotid artery. Simultaneous measurement of blood pressure enabled the calculation of arterial compliance and distensibility. RESULTS: No differences were observed between patients with aortic regurgitation and the control group concerning age, sex, body surface, and mean blood pressure. Pulse pressure was significantly higher in the aortic regurgitation group compared with that in the control group (78±3 versus 48±1mmHg, P<0.01). Arterial compliance and distensibility were significantly greater in the aortic regurgitation group compared with that in the control group (11.0±0.8 versus 8.1±0.7 10-10 N-1 m4, P=0.01 e and 39.3±2.6 versus 31.1±2.0 10-6 N-1 m², P=0.02, respectively). CONCLUSION: Patients with chronic aortic regurgitation have increased arterial distensibility. Greater vascular compliance, to lessen the impact of systolic volume ejected into conduit arteries, represents a compensatory mechanism in left ventricular and arterial system coupling.